UJI EFEKTIVITAS SEDIAAN GEL ANTISEPTIK TANGAN EKSTRAK BUAH PARIA HUTAN (Momordica charantia L.) TERHADAP Staphylococcus aureus - Rusmin Rusmin (Akademi Farmasi Yamasi Makassar, 2022)
The skin is very susceptible to infection or other skin diseases, one of which is caused by the bacterium Staphylococcus aureus. Staphylococcus aureus for 80% of suppurative diseases, with the surface of the skin as its natural habitat. The spread of Staphylococcus aureus is most commonly transmitted from hand to hand. As an effort to prevent infection with Staphylococcus aureus, antiseptic preparations are needed which can prevent infection and are practical in their use. In this study, the effectiveness of hand antiseptic gel extracts from Paria Hutan (Momordica charantia L.) was tested with a concentration of 1% w/v, 2% w/v, 3% w/v and 4% w / v. test bacteria used Staphylococcus aureus. This research was conducted using agar diffusion method. The results showed that the test results of antiseptic hand gel preparation of forest pariah extract with concentrations of 1% w/v, 2% w/v, 3% w/v and 4% w/v met the results of organoleptic evaluation tests, homogeneity, and pH tests (phisical test). Anova analysis results showed that the antiseptic hand gel formulation of extract from fruit of formula V (concentration 4% b/v) provides the most optimal effect in inhibiting the growth of Stapilococus aureus with an average value of inhibition zone diameter 15,7 mm.